Donor‐transmitted malaria after heart transplant managed successfully with artesunate. Issue 6 (1st October 2014) - Sabé, N.; González‐Costello, J.; Oriol, I.; Sánchez‐Salado, J.C.; Ortega, S.; Oliver, E.; Manito, N.; Carratalà, J.
Abstract Donor‐transmitted malaria is a rare complication in solid organ transplantation, which causes high mortality. Data concerning the use of artesunate in solid organ transplant recipients are lacking. We report a heart transplant patient who developed donor‐derived severe Plasmodium falciparum malaria, successfully treated with artesunate. Transmission of malaria to 2 of the other transplant recipients from the same donor was also documented.